The Study of Daytime Ionospheric E‐Region Radar Echoes Simultaneously Observed by Qujing VHF Radar and Multi‐Ionosondes - Yunzhou Zhu; Qiong Tang; Zhongxin Deng; Chen Zhou; Yi Liu; Tong Xu; Zhuangkai Wang; Zhengyu Zhao; Fengsi Wei; Xueshang Feng (Space Weather)
Abstract In this work, the daytime E‐region field‐aligned irregularities (FAIs) observed by the Qujing (geographic 25.64°N, 103.70°E) Very High Frequency coherent backscatter radar was reported. The range spread and enhanced sporadic‐E layer (Es) during the same period of the unusual radar echoes were separately observed by two ionosondes located at the Huize and Qujing. The Huize (geographic 26.51°N, 103.61°E) ionosonde was roughly located underneath the radar scattering volume which measured enhanced and range spread Es layer during this period of the unusual radar echoes, indicating that the daytime E‐region FAIs were closely related to the localized density gradient that embedded within the coordinated Es layer. Fengyun‐4A (FY‐4A) satellite data show that a strong convective activity accompanied by gravity waves occurred near the radar scattering volume region. As a result, we proposed that the gravity waves driven by the convective activity in the lower atmosphere can modulate the Es layers and then generate the daytime FAIs through the polarization process.